Board Tensions and Activist Trustees: Current Domestic Cases and Implications for the Enrollment Manager. Issue 1 (April 2016) - Levine, Jeffrey P.
Abstract : Utilizing five recent highly‐visible case studies of campus tensions between boards of trustees and trustee activism, the researcher examined each case, the history of trustees, the shift in trustee activism, what happened and what can be learned from each case, institutional context, the role of the trustee, and several responses. The researcher concludes by providing specific recommendations to effectively minimize trustee activism and tensions in the future and describes how these tensions specifically affect the university enrollment manager.